Integrating Genome-Wide CNVs Into QTLs and High Confidence GWAScore Regions Identified Positional Candidates for Sheep Economic Traits - Cheng, Jie; Cao, Xiukai; Hanif, Quratulain; Pi, Li; Hu, Linyong; Huang, Yongzhen; Lan, Xianyong; Lei, Chuzhao; Chen, Hong (Frontiers in Genetics, 2020)
Copy number variations (CNVs) are an important source of genetic variations, which can affect a wide range of economic traits by diverse mechanisms. Besides, genome scan has identified lots of quantitative trait loci (QTL) about economically important traits. Meanwhile, genome-wide association studies (GWAS) can localize genetic variants associated with phenotypic variations. Here, we developed a method called GWAScore which could collect GWAS date to identify positional candidate, and we integrated CNVs into QTLs and high confidence GWAScore regions to detect crucial CNV markers for sheep growth traits. We got 197 candidate genes which was annotated by CNVs located in GWAScore regions and QTL. These are some crucial genes (MYLK3, TTC29, HERC6, ABCG2 and RUNX1, etc.) with the higher GWAScore peak values. Among the candidate genes, we identified 23 CNVs located in the exon of genes (HERC6, etc.) and 5 CNVs located in the uptream or 5’UTR of genes (ABCG2, etc.). In this study, we excavate the potential value of candidate genes as markers for the sheep molecular breeding.